Analysis of the Unimplementation of Electronic Medical Records Using the Fishbone Method at the Mojogedang 1 Karanganyare Health Center: Analisis Belum Terlaksananya Rekam Medis Elektronik Menggunakan Metode Fishbone Di Puskesmas Mojogedang 1 Karanganyare - Arfiah, Fauziah Nur; Wariyanti, Astri Sri; Sutrisno, Trismianto Asmo (Universitas Muhammadiyah Sidoarjo, 2025)
Mojogedang 1 Community Health Center has not yet implemented electronic medical records because are still obstacles in the process of implementing electronic medical records. The aim of this research is to analyze the factors that cause electronic medical records to not be implemented. This research design was qualitative with a population of all employee components at the Mojogedang 1 Community Health Center of 60 employees. The sample was 38 people determined using a formula Slovin.Data were collected using observation, unstructured interview guides, and questionnaires. Data analysis uses descriptive. The results of the research show that the factors that have not implemented electronic medical records are influenced by factorsman, material, methode, machine, money. The root of the problem of not implementing electronic medical records is influenced by the lack of a budget. The conclusion of this research is that electronic medical records have not been implemented which are influenced by factorsman, material, methode, machine, money with the main root of the problem being that there is no budget to accelerate the implementation of electronic medical records. The suggestion for Mojogedang 1 Community Health Center is to immediately form a special team to accelerate electronic medical records, create service flows and SOPs, add infrastructure, create a special budget and require the highest policy from Mojogedang 1 Community Health Center.